2010
DOI: 10.2169/internalmedicine.49.3918
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Baclofen on Body Weight Reduction in Obese Subjects: A Pilot Study

Abstract: Background and objective We previously reported that baclofen, a GABAB agonist, reduces body weight in obese mice. In this clinical study, we examined the possibility that baclofen might serve as an effective therapeutic agent for obesity in humans. Methods Seven women and three men ranging from 25-51 years of age and 31.3-41.0 kg/m 2 body mass index were included in the study. Baclofen, which was started at a dose of 15 mg/day and increased to 30 mg/ day in 10 days, was administered for 12 weeks. Results Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…However, individual patients did experience modest losses in weight with the overall group profile indicative of some benefit relative to placebo. Such findings are consistent with an open-label trial in humans (Arima and Oiso, 2010), and research in rats (Patel and Ebenezer 2010), in which baclofen has been reported to reduce body weight, as well as an open-label trial in which sodium oxybate, which also acts as a GABA-B agonist, reduced binge eating and body weight (McElroy et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…However, individual patients did experience modest losses in weight with the overall group profile indicative of some benefit relative to placebo. Such findings are consistent with an open-label trial in humans (Arima and Oiso, 2010), and research in rats (Patel and Ebenezer 2010), in which baclofen has been reported to reduce body weight, as well as an open-label trial in which sodium oxybate, which also acts as a GABA-B agonist, reduced binge eating and body weight (McElroy et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…For example, the GABA-B agonist, baclofen, which has been found to be effective in treating several aspects of alcohol dependence in many (Addolorato et al, 2000, 2007, 2011) but not all studies (Garbutt et al, 2010), has also been shown to aid in the reduction of binge eating behavior in both preclinical and clinical studies (Buda-Levin et al, 2005; Broft et al, 2007; Berner et al, 2009; Corwin et al, 2012). Additionally, baclofen has shown some success in inhibiting weight gain in animals and promoting weight loss in clinical samples (Sato et al, 2007; Arima and Oiso, 2010; Patel and Ebenezer, 2010). …”
mentioning
confidence: 99%
“…Recently, it has been reported that AC treatment activates GABA B1 R as well as decrease PKAα and p-CREB expression, suggesting the involvement of the PKA-CREB pathway in the management of obesity by anthocyanin [ 63 ]. GABA B agonists, such as baclofen, showed the ability to decrease neuropeptide Y (NPY), demonstrating an anti-obesity effect as this decreases human body weight and waist circumference [ 64 ]. NPY had been shown to play a key role in appetite and food intake [ 65 ].…”
Section: Discussionmentioning
confidence: 99%